2020
DOI: 10.1021/acs.chemrestox.0c00012
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of DNA Adducts and Abasic Site Formation in Tissues of Mice Treated with a Nitrogen Mustard

Abstract: Nitrogen mustards (NM) are an important class of chemotherapeutic drugs used in the treatment of malignant tumors. The accepted mechanism of action of NM is through the alkylation of DNA bases. NM-adducts block DNA replication in cancer cells by forming cytotoxic DNA interstrand cross-links. We previously characterized several adducts formed by reaction of bis­(2-chloroethyl)­ethylamine (NM) with calf thymus (CT) DNA and the MDA-MB-231 mammary tumor cell line. The monoalkylated N7-guanine (NM-G) adduct and its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 66 publications
(166 reference statements)
2
9
0
Order By: Relevance
“…The MS 2 spectra collected were consistent with the ones previously reported by Chen and colleagues. 10 Furthermore, the MS 3 spectra collected in our work provided further confirmation of the chemical nature of the modifications. Indeed, the appearance of one of the nucleosides or one of their fragments (Table 1) gives insights into where the modification is located.…”
Section: ■ Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…The MS 2 spectra collected were consistent with the ones previously reported by Chen and colleagues. 10 Furthermore, the MS 3 spectra collected in our work provided further confirmation of the chemical nature of the modifications. Indeed, the appearance of one of the nucleosides or one of their fragments (Table 1) gives insights into where the modification is located.…”
Section: ■ Discussionsupporting
confidence: 60%
“…Specific DNA adducts generated by CPA in vitro and in vivo have been previously evaluated with liquid chromatography–mass spectrometry (LC–MS) methods (Figure ). …”
Section: Introductionmentioning
confidence: 99%
“…Kumar et al once showed that as per 12 and 24 h after exposure to HN2 in hairless mice, obvious DNA oxidative damage, lipid peroxidation, and inflammation were observed. However, for HN2-treated female mice, the mono-alkylated N 7 -guanine adduct reached a maximum level within 6 h in the liver, lung, and spleen . It is thus speculated that, for these three NMs, HN1 with moderate cytotoxicity was more likely to promote endogenous acetaldehyde production and inflammation than less toxic HN3.…”
Section: Resultsmentioning
confidence: 97%
“…However, for HN2-treated female mice, the monoalkylated N 7 -guanine adduct reached a maximum level within 6 h in the liver, lung, and spleen. 32 It is thus speculated that, for these three NMs, HN1 with moderate cytotoxicity was more likely to promote endogenous acetaldehyde production and inflammation than less toxic HN3. Nonetheless, HN2 with the highest toxicity may have a stronger direct damage effect on cells, but a weaker lipid peroxidation and inflammatory response.…”
Section: Inhibitory Concentration Of Five Nmsmentioning
confidence: 99%
See 1 more Smart Citation